Frequency and approaches in treatment of fractured condylar processes - Milosavljević, Sara S; Ranđelović, Jelena; Pešić, Zoran (Medicinski podmladak, 2018)
Introduction: The condyloid process or condylar process (Lat. processus condylaris)is the second, more posterior process on the mandible, which takes part in the formation of the temporomandibular joint. Fractures of the condyloid process constitute 25% to 35% of all fractures of the mandible. They rarely occur isolated, whereas they are oftener associated with fractures of other localizations on the mandible. The aim: This paper aims at determining the frequency of the fracture of the condyloid process of the mandible in relation to fractures of other localizations; the mechanisms of injury occurrence; as well as the representation of individual surgical procedures within the treatment. Material and Methodology: The data obtained from the medical documentation of the Department for Maxillofacial Surgery, the Stomatology Clinic of Niš were analyzed using clinical retrospective study in the period from January 2011 to December 2017. Results: The analysis of the medical documentation established that 343 patients having mandible fractures, out of which 85 patients (24.78%) had mandible fractures, were treated at the Clinic for Stomatology of Nis, at the Maxillofacial Surgery Department in the aforementioned period. Conclusion: It was stated that the mandible fracture most frequently lead to the occurrence of fracture of its condyloid process. Most frequently it occurs with men at the age of 21-40 as the consequence of traffic accidents. Key words: Fractures of the condyloid process, the mechanism of occurrence, therapy